2017
DOI: 10.1007/s11882-017-0733-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parasitic Worm Infections on Allergy Diagnosis in Sub-Saharan Africa

Abstract: Epidemiological studies from Sub-Saharan Africa indicate that allergies are on the rise in this region especially in urban compared to rural areas. This increase has been linked to improved hygiene, lifestyle changes, and lower exposure to pathogens in childhood. Reduced exposure to parasitic worm (helminth) infections and allergy outcomes has been the focus of a number of population studies over the years. Paradoxically, there are parallels in the immune responses to helminths and to allergies. Both condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 81 publications
(99 reference statements)
0
25
0
Order By: Relevance
“…Some studies defined IgE values of 100-1000kU/L as "high IgE level", and IgE ≥ 1000 kU/L as "very high" [32][33][34]. Very low or absent IgE levels may be found in patients with allergic rhinitis-, chronic sinusitis-like symptoms and asthma [32,36,37,58] Cannot exclude atopic/allergic or parasitic conditions Biomarker for atopy/allergy [29,44,45,53,55], parasitosis [71][72][73] Might potentially be used as a marker for higher cancer susceptibility [32][33][34] Some patients with normal IgE levels may have higher rates of malignancy [18,20] In general, elevated IgE levels are associated with lower rates and risk for malignancy [17,20,21,142]. Very high and extremely high total serum IgE levels are seen in certain malignancies such as lymphoma [146] and IgE myeloma [147] May be a sensitive and specific marker for CVID (Common Variable Immunodeficiency) when there is high suspicion for primary humoral deficiency [38] Cannot exclude immunodeficiency Elevated IgE levels may raise suspicion for certain immunodeficiencies in appropriate patients (e.g.…”
Section: Overview Of Medical Conditions Which Are Associated With Altmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies defined IgE values of 100-1000kU/L as "high IgE level", and IgE ≥ 1000 kU/L as "very high" [32][33][34]. Very low or absent IgE levels may be found in patients with allergic rhinitis-, chronic sinusitis-like symptoms and asthma [32,36,37,58] Cannot exclude atopic/allergic or parasitic conditions Biomarker for atopy/allergy [29,44,45,53,55], parasitosis [71][72][73] Might potentially be used as a marker for higher cancer susceptibility [32][33][34] Some patients with normal IgE levels may have higher rates of malignancy [18,20] In general, elevated IgE levels are associated with lower rates and risk for malignancy [17,20,21,142]. Very high and extremely high total serum IgE levels are seen in certain malignancies such as lymphoma [146] and IgE myeloma [147] May be a sensitive and specific marker for CVID (Common Variable Immunodeficiency) when there is high suspicion for primary humoral deficiency [38] Cannot exclude immunodeficiency Elevated IgE levels may raise suspicion for certain immunodeficiencies in appropriate patients (e.g.…”
Section: Overview Of Medical Conditions Which Are Associated With Altmentioning
confidence: 99%
“…Similarly to the atopic/allergic status, the response to parasitic infections is also associated with the induction of strong Th2 immune responses, leading to eosinophilia, elevated Th2 cytokines and increased serum IgE (e.g. in a cohort of patients with Ascaris infection, total IgE levels reached 13,000 kU/L) [71, 72 ]. Moreover, total IgE levels significantly decrease after treatment for E. histolytica, H. nana or A. lumbricoides [73 ].…”
Section: Part 4 Total and Specific Ige As Biomarkers In Parasitic Inmentioning
confidence: 99%
“…We demonstrate similar findings with a high prevalence of allergic and eosinophilic inflammation that is notably most prominent in severe asthma which was associated with elevated eosinophils and FeNO levels. Interestingly, the prevalence of HIV and the presence of parasitic infection was very low in this cohort, thus ensuring that these potential confounders of eosinophilia did not impact the high prevalence rates noted in the cohort 36. The high rates of allergic sensitisation may be a result of geographical location, as the study sites were in large urban areas where exposure to allergens is higher.…”
Section: Discussionmentioning
confidence: 82%
“…Allergen‐specific IgE is the defining characteristic of atopy, and in high‐income countries, allergen‐specific IgE strongly correlates with functional allergy measured by SPT reactivity. However, in helminth‐endemic areas (especially rural areas of low socioeconomic status), this relationship often breaks down . Furthermore, multiple epidemiological studies have shown a positive association between antihelminth IgE (ascariasis, schistosomiasis, filariasis) and wheeze and/or atopy .…”
Section: Helminths and Modulation Of Allergic Disease: The Role Of Immentioning
confidence: 99%
“…Therefore, these cross‐reactive responses have the potential to block clinical responses to allergens like peanut . Further studies are needed to clarify whether high levels of circulating cross‐reactive protein or carbohydrate‐specific IgE are instrumental in inducing or preventing allergic (skin) reactivity …”
Section: Helminths and Modulation Of Allergic Disease: The Role Of Immentioning
confidence: 99%